Impacts of WNT1-inducible signaling pathway protein 1 polymorphism on hepatocellular carcinoma development. - Chih-Tien Chen; Hsiang-Lin Lee; Hui-Ling Chiou; Chia-Hsuan Chou; Po-Hui Wang; Shun-Fa Yang; Ying-Erh Chou (PLoS ONE)
Background WNT1-inducible signaling pathway protein 1 (WISP1) is a member of CCN protein family and a downstream target of β-catenin. Aberrant WISP1 expression is associated with carcinogenesis. In the current study, we focused on examining WISP1 single nucleotide polymorphisms (SNPs) to elucidate hepatocellular carcinoma (HCC) clinicopathologic characteristics. Methodology/principal findings The WISP1 SNPs rs2977530, rs2977537, rs2929973, rs2929970, rs62514004, and rs16893344 were analyzed by real-time polymerase chain reaction in 332 patients with HCC and 664 cancer-free controls. Results The patients with higher frequencies of WISP1 rs62514004 (AG + GG) and rs16893344 (CT + TT) variants revealed a lower risk to reach a later clinical stage compared with their wild-type carriers. Furthermore, individuals who carried WISP1 rs62514004 and rs16893344 haplotype G-T showed a greater synergistic effect combined with alcohol drinking on HCC development (AOR = 26.590, 95% CI = 9.780-72.295). Conclusions Our results demonstrated that the HCC patients with WISP1 SNPs are associated with HCC development, and WISP1 SNPs may serve as markers or therapeutic targets for HCC.